Efectividad de las presiones de sello en la vía aérea con la máscara laríngea clásica y la supreme en pacientes adultos sometidos a cirugía oftalmológica por personal de anestesia en entrenamiento (2009)
ABSTRACT: Introduction: New anaesthetic techniques mean that devices must be developed which provide advantages in terms of sealing pressure and ventilation (without intubation's sympathetic system component). This study involved a new extraglotic device which was inserted by personnel undergoing training in the use of anaesthesia during ophthalmology surgery. The main objective was to compare differences in airway sealing pressure in Latin-American adults undergoing outpatient ophthalmology surgery when two types of extraglotic devices were inserted by trainee medical personnel. The secondary objectives involved comparing insertion time, percentage ventilatory success rate and evidence of postoperative airway trauma. Methods: This was a randomised, double-blind, clinical trial which compared the effectiveness of the classic laryngeal mask airway (CLMA) to the laryngeal mask airway Supreme (LMA-S) to ensure airway sealing pressure in 97 ASA I-III adults having no difficult airway predictors who were undergoing programmed ophthalmology surgery. Results: LMA-S reached higher mean sealing pressures at the beginning (24.2cm H2O cf 19.2cm H2O) and at the end of the procedure (24.6cm cf 20.4cm H2O) (p<0.05). Insertion times were similar and there was no difference in the incidence of postoperative adverse effects. Conclusions: LMA-S achieved a higher mean sealing pressure than CLMA. They had similar insertion times and adverse effect incidence when trainee medical inserted them into adult patients undergoing outpatient ophthalmology surgery.